2017
DOI: 10.1039/c7ra06186b
|View full text |Cite
|
Sign up to set email alerts
|

A simple and convenient method to fabricate new types of phytic acid–metal conversion coatings with excellent anti-corrosion performance on the iron substrate

Abstract: A simple and practical method was developed to prepare phytic acid–metal complex coatings with excellent anti-corrosion performance on the iron substrate by making full use of the bridging effect of metal ions in the film-forming solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 45 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…Phytic acid (PA) is a natural phosphorus resource and is abundant in seeds and grains in plants, which contains six phosphate groups and has a strong chelating ability. [33,34] The materials derived from phytic acid have been shown to exhibit high electrocatalytic activity, [35] and serve as anti-corrosion materials [36] and adsorbents. [37,38] Remarkably Kurungot and coworkers reported that PAÀ Fe xerogel (PA:Fe 3 + = 1 : 1) had high proton conductivity of 2.4 × 10 À 2 S cm À 1 at 120 °C and was used as proton conductor, [39] which was proved by the study of linear fuel cell polarization with the conduction of protons across the pelletized xerogel.…”
Section: Introductionmentioning
confidence: 99%
“…Phytic acid (PA) is a natural phosphorus resource and is abundant in seeds and grains in plants, which contains six phosphate groups and has a strong chelating ability. [33,34] The materials derived from phytic acid have been shown to exhibit high electrocatalytic activity, [35] and serve as anti-corrosion materials [36] and adsorbents. [37,38] Remarkably Kurungot and coworkers reported that PAÀ Fe xerogel (PA:Fe 3 + = 1 : 1) had high proton conductivity of 2.4 × 10 À 2 S cm À 1 at 120 °C and was used as proton conductor, [39] which was proved by the study of linear fuel cell polarization with the conduction of protons across the pelletized xerogel.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 3a, four peaks centered at 533 eV, 284.7 eV, 228 eV and 171 eV 29 can be clearly seen, which correspond to the O 1s, C 1s, and P 2p signals, respectively. Note that the 228 eV and 171 eV peaks should belong to the energy loss line of P due to the machine limitations.…”
Section: Resultsmentioning
confidence: 91%
“…[ 22 ] The atomic force microscopy (AFM) tests exhibit the different thicknesses are ≈301, ≈253, and ≈336 nm for PA‐Zn, PA‐Co, and PA‐Ni films, respectively (Figure S4a–f, Supporting Information), as a result of the complexation ability of metal ions with phytic acid and the film compactness. [ 23 ] The root‐mean‐square (RMS) roughness value was calculated to be 10.7 nm for the pure Zn foil, but significantly increased to 34.7, 43.9, and 45.4 nm after coating of PA‐Zn, PA‐Co, and PA‐Ni film due to the formation of nanostructured grains. Furthermore, the Young's modulus of PA‐Zn, PA‐Co, and PA‐Ni films were calculated to be 28.7, 12.2, and 16.7 Gpa through the force–separation curves (Figure S4g–i, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%